Transforming Early Childhood in England: Towards a Democratic Education - Cameron, Claire; Moss, Peter (UCL Press, 2020)
Early childhood education and care has been a political priority in England since 1997, when government finally turned its attention to this long-neglected area. Public funding has increased, policy initiatives have proliferated and at each general election political parties aim to outbid each other in their offer to families. Transforming Early Childhood in England: Towards a Democratic Education argues that, despite this attention, the system of early childhood services remains flawed and dysfunctional. National discourse is dominated by the cost and availability of childcare at the expense of holistic education, while a hotchpotch of fragmented provision staffed by a devalued workforce struggles with a culture of targets and measurement. With such deep-rooted problems, early childhood education and care in England is beyond minor improvements. In the context of austerity measures affecting many young families, transformative change is urgent. Transforming Early Childhood in England offers a critical analysis of the current system and proposes change based on young children’s universal right to education. The book calls for provision built on democratic principles, where all learning by all children is visible and recognised, educators are trusted and respected, and a calmer approach called ‘slow pedagogy’ replaces outcomes-driven targets. Combining criticism and hope, and drawing on inspiring research and examples from home and abroad, the book is essential reading for students, educators, practitioners, parents, academics and policymakers - anyone, in fact, who seeks to understand the policy problems for early childhood education and care in England, and see better prospects for the future.